Função social da propriedade e Direito Econômico - Abdulmassih, Thiago Brazolin (2017)
The present study aims to relate the theory of the social function of property to the contributions made by the field of Economic Law. At first, it explores the history of private property, making use of the philosophical theories which tried to justify the problem of private property. Dealing with the assumptions of the Economic Law School of the Pontifícia Universidade Católica de São Paulo, the ideas of John Locke and Jacques Maritain are brought, to expose the foundation of private property and humanism within political and economic relations. Approaching property relations within the scope of Economic Law, a brief history of its evolution that came to a head with the creation of a legal order of deontological nature, which acts upon the economy, a de facto universality of ontological nature. In this issue, Goffredo Telles Junior’s theory of Direito Quântico is used to reveal the human dignity with legal statutes, and the importance of Human Rights in relation to private property for the strengthening of Democracy. In an effort to narrow the scope of the research, there is an exposition on the legal theories pertaining the concept of estate, property and domain, so that the difference between dynamic and static property can be traced, focusing on the first, which is directed to the production of other goods. The study proceeds with a comparison among foreign legal orders, concluding for the narrow relation between the legal protection of property and the respect of its purpose, which must be socially useful. The research then explores the Brazilian legislation, from the first constitutions to the current Civil Code, to demonstrate that the means of production, the so-called dynamic property, comprises a specific legal situation, that must reconcile the value of work and self-initiative, as well as social justice. Based upon the legislation, this paper addresses examples where property, when it respects its social role, bring systemic growth of the economy and human dignity, as, regarding the constitutional economic order, cannot be set apart